Applying reproductive technologies and genome resource banking to laboratory animals - S. Ya. Amstislavsky; E. Yu. Brusentsev; T. O. Abramova; D. S. Ragaeva; I. N. Rozhkova; T. N. Igonina; E. A. Kizilova; V. A. Naprimerov; N. Yu. Feoktistoiva (Вавиловский журнал генетики и селекции)
The Genome Resource Bank (GRB) is a repository of frozen biological material, including semen and embryos. Cryobanking is used in combination with modern reproductive technologies such as rederivation, in vitro culture and embryo transfer. Thirteen mouse and rat strains have been re-derived and 32 are kept frozen in the cryostorage at the Institute of Cytology and Genetics, Novosibirsk. Some other laboratory animal species have been cryopreserved as well. Embryos of two hamster species (Djungarian and Campbell’s) in the genus Phodopus were cryopreserved and the viability of thawed embryos was proved by their successful development in vitro and in vivo (by transfer to a recipient). A positive effect of the granulocyte-macrophage colony-stimulating factor (GM-CSF) was demonstrated with both these Phodopus species. Furthermore, semen of Djungarian (Phodopus sungorus) and Campbell’s (Phodopus campbelli) hamsters, domestic cat (Felis catus), amur cat (Prionailurus bengalensis euptilurus) and bobcat (Lynx rufus) was frozen and cryopreserved. Double staining by SYBR Green/PI and subsequent confocal microscopy demonstrated that more than 40 % of amur cat semen retained viability after cryopreservation. This is the world’s first reported successful freezing of semen of this wild felid (Prionailurus bengalensis euptilurus). This article reviews the results and discusses prospects of using reproductive technologies for conservation of laboratory species.